The development policy system under pressure: acknowledging limitations, sourcing advantages and moving towards a broader perspective - Victoria Gonsior; Stephan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
This paper uses the development policy system as an entry point assuming that various fundamental changes along three dimensions – narratives (why?), strategies (what?) and operational approaches (how?) – can be observed over recent years. Changes are diverse, ranging from new narratives translated to the development policy context (such as the migration narrative) to strategic considerations (for instance, developing countries' graduation implications), new instruments (in form of development finance at the interface with the private sector), and concepts for project implementation (including frontier technology). We discuss the implications and effects of these trends in terms of holistic changes to the wider development policy system itself. Do these changes go hand-in-hand with and ultimately build on and re-inform each other? Or are we actually observing a disconnect between the narratives that frame the engagement of actors in development policy, their strategies for delivery, and operational approaches in partner countries? Based on a consultation of the appropriate literature and information gathered during a number of expert interviews and brainstorming sessions, this paper sheds light on these questions by exploring current trends and by highlighting continuing disconnections between the “why”, “what” and “how” in the development policy system. Further, we argue that the importance of such disconnections is increasing. In particular, the persistent or even increasing disconnections in the development policy system can be more problematic in the face of a universal agenda and the need to upscale delivery to achieve the Sustainable Development Goals (SDGs).
Keywords: 330; Agenda 2030; Regionale + globale + transnationale Governance